1996
DOI: 10.1021/om9602015
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of CO and CNR into Tantalum−Methyl Bonds of Imido(pentamethylcyclopentadienyl)tantalum Complexes. X-ray Crystal Structures of [TaCp*(NR)Me{η2-C(Me)NR}] and [TaCp*Cl(O){η2-C(Me)NR}] (R = 2,6-Me2C6H3)

Abstract: TaCp*Cl 2 {N(2,6-Me 2 C 6 H 3 )}] reacts with 2 equiv of LiMe at -78 °C to give the imido dimethyl complex TaCp*Me 2 {N(2,6-Me 2 C 6 H 3 )} (1) in almost quantitative yield, whereas the monomethyl imido derivatives [TaCp*MeX{N(2,6-Me 2 C 6 H 3 )}] (X ) Cl (2), OC 6 H 3 Me 2 (3)) can be prepared by addition of HX (X ) Cl, OC 6 H 3 Me 2 ) to toluene solutions of [TaCp*Me-(NR){NR(CMedCMe 2 )}] (R ) 2,6-Me 2 C 6 H 3 ) with elimination of the corresponding imine RNdCMeCHMe 2 . Complex 1 reacts with CO to give the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
45
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 44 publications
(27 reference statements)
11
45
0
Order By: Relevance
“…It was observed that for monocyclopentadienyl imido tantalum derivatives addition of a second CNR molecule into the iminoacyl compounds [TaCp*(NR)X{η 2 -C(Me)=NR}] (R = 2,6-Me 2 C 6 H 3 , tBu; X = Cl, Me) resulted in differing behaviours depending on the R group of the imido ligand. No reaction was found for R = 2,6-Me 2 C 6 H 3 , [10] whereas a second insertion occurred for R = tBu. [20] Conversely, the imido complexes [TaCp*MeX(NR)] (R = 2,6-Me 2 C 6 H 3 , tBu; X = Cl, Me) reacted with CO to give the dinuclear compound [TaCp*(NR)Me] 2 {µ-η 2 -OC-(Me)=C(Me)O} for X = Me [10] and one of the few mononuclear derivatives [TaCp*Cl(O){η 2 -C(Me)=NR}] containing a terminal tantalum-oxo double bond for X = Cl.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…It was observed that for monocyclopentadienyl imido tantalum derivatives addition of a second CNR molecule into the iminoacyl compounds [TaCp*(NR)X{η 2 -C(Me)=NR}] (R = 2,6-Me 2 C 6 H 3 , tBu; X = Cl, Me) resulted in differing behaviours depending on the R group of the imido ligand. No reaction was found for R = 2,6-Me 2 C 6 H 3 , [10] whereas a second insertion occurred for R = tBu. [20] Conversely, the imido complexes [TaCp*MeX(NR)] (R = 2,6-Me 2 C 6 H 3 , tBu; X = Cl, Me) reacted with CO to give the dinuclear compound [TaCp*(NR)Me] 2 {µ-η 2 -OC-(Me)=C(Me)O} for X = Me [10] and one of the few mononuclear derivatives [TaCp*Cl(O){η 2 -C(Me)=NR}] containing a terminal tantalum-oxo double bond for X = Cl.…”
Section: Introductionmentioning
confidence: 92%
“…[1] For a given metal atom, the stability and further evolution of these compounds are determined by the nature of the ancillary ligands. Many reaction pathways may follow to give a broad variety of products: [1] (a) migratory insertion of a second alkyl or aryl group to give η 2 -imine or η 2 -ketene complexes; [2][3][4][5] (b) intra-or intermolecular coupling of iminoacyl or acyl units affording diaza-or dioxobutene complexes; [6,7] (c) transfer of the NR or O moieties to the metal centre; [8][9][10][11] (d) insertion of a second CNR [12][13][14][15][16] or CO [17] molecule into the new M-C bond formed after the first insertion process and (e) hydrogen migration. [18,19] We reported the results of our studies on the insertion reactions of CNR into the Ta-C(methyl) bond of monocyclopentadienyl complexes of the type [TaCp*Cl x Me 4-x ] [8][9][10] for which processes (a) and (c) were observed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38][39][40] However, the insertion reaction was not observed, rather displacement of the coordinated MMA and MA ligands (Scheme 4) gave the carbonyl derivatives [NbCp R Cl 2 (CO) 2 ] 2 [Cp R = C 5 H 4 SiMe 2 Cl (9), Cp R = C 5 H 4 SiMe 3 (10)] for the reaction with CO, although we could not characterize the corresponding organometallic species resulting from the reaction with CNAr (Scheme 4). Therefore, the formally Nb V starting compounds 2-3 undergo a reductive decoupling to the Nb III derivatives.…”
Section: (E = B Al)mentioning
confidence: 99%